Profil Tajam Penglihatan Pengendara Ojek Online di Kelurahan Keputih Surabaya - IZDIHAR, VEYSHA; SAYOGO, WILLIAM; TANDEAN, VICTOR SETIAWAN (Universitas Hang Tuah, 2026)
Visual acuity is an important factor influencing driving safety, particularly among online motorcycle taxi drivers who work with high visual exposure and varying road conditions. Visual acuity plays a critical role in driver’s ability to detect road hazards, interpret traffic signs, and respond to dynamic traffic situations. Because online motorcycle taxi drivers frequently operate for extended hours which they are exposed to sunlight, glare, dust, wind, and prolonged screen use when interacting with customers and navigation applications which can affect eye comfort and performance. These occupational stressors may contribute to reduced visual efficiency, emphasizing the importance of regular monitoring. This study aims to determine the visual acuity profile of online motorcycle taxi drivers in Keputih Surabaya subdistrict. A descriptive observational design with a cross-sectional approach was used, involving 70 respondents. Visual acuity was examined using a Snellen chart and pinhole test and classified according to the World Health Organization standards. The results showed that 34 respondents (48.57%) had refractive errors, 27 respondents (38.57%) had normal visual acuity, and 9 respondents (12.86%) had non-refractive visual impairments. The majority of respondents with refractive errors remained within the normal visual acuity category (85.29%).